ANALISIS PENGETAHUAN REMAJA PUTRI DALAM MENANGANI DISMENORE DI SMK SEHATI JURUSAN KEPERAWATAN TAHUN 2024 - Euis Atikah; Yayuk Sri Rahayu; Rina Dwi Anggraeni (Bajang Institute, 2024)
Knowledge is the result of knowing, and this happens after people sense certain objects. Sensing occurs through the five human senses, namely the senses of sight, hearing, smell, taste and touch. This study aims to analyze the knowledge of adolescent girls in dealing with dysmenorrhea at SMK Sehati, Department of Nursing in 2024. This research method is quantitative by using Analytical Descriptive with sampling using a total sampling of 52 samples. The instrument used in the questionnaire. The results of the Disminore Putri's knowledge about dysmenorrhea who had good knowledge during the pretest was 22 (42.3%) and poor knowledge as many as 30 people (57.7%). After the posttest, 42 students (80.8%) had good knowledge and 10 people (19.2%) had less knowledge. The data analysis used was univariate and bivariate analysis with the chi test of chi square statistics found p-value=0.000. These results show that there is a relationship between knowledge of adolescent girls in dealing with dysmenorrhea at SMK Sehati, Department of Nursing. Conclusion After the intervention was carried out, knowledge about dysmenorrhea in female students at SMK Sehati in the Department of Nursing increased significantly It is hoped that young women at SMK Sehati will seek more information about knowledge in dealing with dysmenorrhea so that they have a broader insight in dealing with dysmenorrhea compared to people who have less knowledge